SYSTEMIC REFORM OF CHINESE ANTICORRUPTION LEGISLATION AND ENFORCEMENT PRACTICE - L. Hongyan (Правоприменение)
The subject. The article is devoted to the analysis of ongoing systematic reform of Chinese anticorruption legislation and practice of its enforcement.The purpose of the article is to formulate ways of improvement Chinese anti-corruption legislation.The methods of legislation analysis and synthesis of legislative gaps and contradictions are used.The results, scope of application. Nowadays, China is moving from the struggle against corruption by political means to the struggle by legal means. In attempt to construct a system of anti-corruption legislation, China is actively forming a dualistic normative system and a mechanism for the interaction between party norms and state legislation. A multilevel vertical-integrated system of anti-corruption legislation with "The anti-corruption law" as a core was created; the Party is stressing the priority status of preventive legislation and the auxiliary role of legislation on control over power. This system should became the basis for building Chinese anti-corruption legislation. The author formulated a system of principles of Chinese anti-corruption legislation, including the principles of efficiency, consistency, economy and gradualism. The importance of the anti-corruption legislative program, the task formulated in 2015, is underlined. The list of the main anti-corruption legislative acts has been determined, including legislation in the aspects "do not dare to take [bribes]", "cannot take [bribes]" and "do not want to take [bribes]". The problem of improving the legislation in the "do not dare to take" aspect have been specially considered, including improvement of criminal legislation, adoption of the law on accountability and responsibility of public servants, as well as the adoption of an anti-corruption law. The main alternatives and problems of improving legislation in the context of "not being able to take" are considered, such as adoption of laws on declaration of property of public servants, on pre-vention of conflict of interests, on transparency of the administration, on public hearings, and the improvement of party norms.Conclusions. China is experiencing a crucial turning point in the fight against corruption since the beginning of the modernization transformation and is in the strategic "window of opportunities". Active and systematic construction of anti-corruption legislation, the transit from formal counteraction to real counteraction is the key to overcoming the current "corruption crisis with Chinese characteristics".